Electrochemical evidence for in situ microbial activity at the Deep Mine Microbial Observatory (DeMMO), South Dakota, USA. Issue 2 (14th November 2020) - Rowe, Annette R.; Abuyen, Karla; Lam, Bonita R.; Kruger, Brittany; Casar, Caitlin P.; Osburn, Magdalena R.; El‐Naggar, Mohamed Y.; Amend, Jan P.
Abstract: The subsurface is Earth's largest reservoir of biomass. Micro‐organisms are the dominant lifeforms in this habitat, but the nature of their in situ activities remains largely unresolved. At the Deep Mine Microbial Observatory (DeMMO) located in the Sanford Underground Research Facility (SURF) in Lead, South Dakota (USA), we performed in situ electrochemical incubations designed to assess the potential for deep groundwater microbial communities to utilize extracellular electron transfer to support microbial respiration. DeMMO 4 was chosen for its stable geochemistry and microbial community. Graphite and indium tin oxide electrodes poised at −200 mV versus SHE were incubated along with open circuit controls and various minerals in a parallel flow reactor that split access to fluids across different treatments. From the patterns of net current over time (fluctuating between anodic and cathodic currents over the course of a few days to weeks) and the catalytic features measured using periodic cyclic voltammetry, evidence of both oxidative and reductive microbe‐electrode interactions was observed. The predominant catalytic activity ranged from −210 to −120 mV. The observed temporal variability in electrochemical activity was unexpected given the documented stability in major geochemical parameters. This suggests that the accessed fluids are more heterogeneous in electrochemically active microbial populations than previously predicted from the stable community composition. As previously reported, the fracture fluid and surface‐attached microbial communities at SURF differed significantly. However, only minimal differences in community composition were observed between poised potential electrodes, open circuit electrodes, and mineral incubations. These data support that in this environment the ability to attach to surfaces is a stronger driver of microbial community structure than the type or reactivity of the surface. We demonstrate that insight into specific activities can be gained from electrochemical methods, specifically chronoamperometry coupled with routine cyclic voltammetry, which provide a sensitive approach to evaluate microbial activities in situ.